2019
DOI: 10.1002/fuce.201800183
|View full text |Cite
|
Sign up to set email alerts
|

Transition Cycles during Operation of a Reversible Solid Oxide Electrolyzer/Fuel Cell (rSOC) System

Abstract: Reversible high temperature solid oxide cells (rSOC) can be operated both in the fuel cell (SOFC) and the electrolysis mode (SOEC). This specificity is a promising way to either store intermittent renewable energy surpluses by producing H2, or generate electricity from H2 or any other fuel locally available (CH4, biogas) when demand overtakes the local production. Therefore, rSOC technology could reinforce autonomy and flexibility in buildings, eco‐districts, up to industrial sites and local energy grids power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…Aicart et al [20] reported transitions of 10 minutes or less at the stack level between three different power levels and operating modes (SOEC, SOFC-H2, SOFC-CH4). These results were integrated in a natural-gas compatible hybrid storage solution that combined a cathodesupported stack, an after-burner for co-generation, as well as a dual stage H2 compression system for H2 storage up to 185 bars [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aicart et al [20] reported transitions of 10 minutes or less at the stack level between three different power levels and operating modes (SOEC, SOFC-H2, SOFC-CH4). These results were integrated in a natural-gas compatible hybrid storage solution that combined a cathodesupported stack, an after-burner for co-generation, as well as a dual stage H2 compression system for H2 storage up to 185 bars [21].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 15 years, CEA-Liten has dedicated a research program to high temperature electrolysis (HTE), with SOEC testing at various scale combined with multi-scale modeling [15], [28]- [30], stack design and assembly [31], and more recently, small scale rSOC system design, commissioning and operation [20], [32], [33]. To support the current trend of larger module development, CEA has constructed the "Multistack" testing platform which currently allows investigating rSOC modules up to 120 kWDC maximum power.…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of tests of solid oxide cells (SOC) and stacks report on either constant galvanostatic or potentiostatic operation of the SOC [4][5][6][7][8], significantly fewer results have been reported on reversible SOFC/SOEC operation of SOC [9][10][11][12]. Nevertheless, considering the fluctuating nature of renewable energy sources such as wind and solar, the reversible operation of SOC (rSOC), an attractive feature of the technology as rSOC, can provide flexible and up-scalable solutions for conversion and storage of renewable energy; and this paper will focus on flexible load cycling operation of both single cells and stacks.…”
Section: Introductionmentioning
confidence: 99%
“…In conventional solid oxide electrolysis cells (SOECs), Ni-based cermets are commonly employed as the fuel electrodes (cathodes) [4][5][6][7][8][9][10][11][12][13][14][15] . Their microstructure, however, is sensitive to redox conditions that dominate co-electrolysis, causing significant losses in electrical conductivity and electrocatalytic activity during long-term operation 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In conventional solid oxide electrolysis cells (SOECs), Ni-based cermets are commonly employed as the fuel electrodes (cathodes). Their microstructure, however, is sensitive to redox conditions that dominate co-electrolysis, causing significant losses in electrical conductivity and electrocatalytic activity during long-term operation . To maintain stable performance, reducing agents, such as hydrogen or carbon monoxide, are co-fed with steam and/or carbon dioxide to prevent Ni-oxidation. At the same time, oxygen formed at the cathode is recovered through the solid electrolyte and is routinely evolved into an air stream at the anode.…”
Section: Introductionmentioning
confidence: 99%